Acupuncture-related peripheral stimulation as a candidate neuromodulatory model of insomnia: clinical evidence, sleep-wake circuitry, and translational limits - He Ming; Jie Yuan; Jiao Liang; Penglong Yu (Frontiers in Neuroscience, 2026)
Acupuncture-related peripheral stimulation is often discussed as a non-pharmacological option for insomnia disorder, but its relevance to sleep neuroscience depends on more than improvement in sleep questionnaires. This critical narrative Review evaluates whether acupuncture and related acupoint-based stimulation methods can serve as testable peripheral models of sleep–wake and hyperarousal circuitry. Across clinical studies, the most consistent signal is improvement in subjective sleep quality and insomnia severity in selected populations. Evidence for objective sleep architecture, multiday sleep–wake stability, relapse prevention, and biomarker-mediated clinical response remains less secure. Human neuroimaging studies provide emerging but still associative evidence involving locus coeruleus, hypothalamic, insular, limbic–prefrontal, and thalamocortical networks. Electrophysiological, autonomic, endocrine, neurochemical, and microbiota–gut–brain findings are biologically plausible, but their proximity to human chronic insomnia disorder varies substantially. Safety is generally favorable when appropriately delivered, although adverse-event reporting remains inconsistent and comparative cost-effectiveness against CBT-I or pharmacotherapy is unestablished. We propose that acupuncture-related stimulation should currently be evaluated as an adjunctive, preference-sensitive, and mechanistically testable approach rather than as a replacement for cognitive behavioral therapy for insomnia. Its translational credibility will depend on credible comparators, objective sleep physiology, expectancy assessment, and prespecified mediation analyses.